Effects of a glycogenic additive on intake, daily gain, and blood metabolites in weaned horses - Morones, Eduardo; Pérez-Estrada, Paulina; Mendoza-Martínez, Germán; Hernández-García, Abel; Martínez-García, Antonio (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2020)
The objective of this experiment was to evaluate a glycogenic feed additive in terms of performance and response in blood metabolites in weaned horses. Twenty weaned horses of the Unidad de Policía Montada Metropolitana del Ministerio de Seguridad Pública del Gobierno de la Ciudad de México, México, were randomly assigned to two treatment groups: control or an oral dose of the glycogenic additive (10 g/d). The additive was based on propylene glycol and Na/Ca propionate and was supplied for 30 days. Data were tested for normality and initial weight was used as a covariate for analyzing the average daily gain (ADG). The ADG was negatively affected (P < 0.01) by the glycogenic compound (0.468 vs. 0.517 kg), while there were no significant differences (P > 0.10) in blood glucose, globulins, total glucose, triglycerides, cholesterol, creatinine or urea in horses from either treatment group. It was concluded that the glucogenic additive, based on propylene glycol and Na/Ca propionate, negatively affected the performance of the horses. Therefore, administration of the additive is not recommended in weaned horses. Highlights From: Use of glycogenic additive in weaned horses. In weaned horses they did not show changes in blood metabolites with the use of a glycogenic additive. Glycogenic additive, did not increase weight change in weaned horses. The supplementation of a glycogenic additive negatively affected the productive performance (ADG) in weaned horses.